RELIGIOUSITY, LOCATION, AND ISLAMIC WORK PERFORMANCE: THE CONNECTION BETWEEN INDONESIAN AND MALAYSIAN EMPLOYEES - Fahrullah, A'rasy; Anwar, Moch. Khoirul; Suryaningsih, Sri Abidah; Fahmi, Moh. Farih; Masrizal, Masrizal; Mohd Noh, Mohd Shahid bin (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: In today's dynamic era, tight competition urges a comprehensive analysis of company success factors with an emphasis on high-quality human resources, employee performance, religiosity, and workplace location's impact on performance. Methods: This explanatory research uses a quantitative approach, surveying 259 urban Muslim employees in Indonesia and Malaysia online from May to August 2023 via random sampling and SEM analysis. Results: Using WarpPLS, this study found that work location significantly affects both religiosity and Islamic work performance, confirming H1 with a coefficient of 0.502 (p-value <0.001) and H2 with a coefficient of 0.573 (p-value <0.001). However, H3 is rejected, as religiosity does not significantly affect Islamic work performance (coefficient 0.082, p-value 0.245). Conclusion and suggestion: Work location significantly affects employee religiosity and Islamic work performance, with urban and closer locations enhancing these aspects. However, religiosity does not directly impact performance, indicating a complex relationship. Managers should consider location in recruitment, support religious practices, and investigate these dynamics while integrating religious values in training programs.